The american duplicity vis-a-vis the colonial problem of the Maghreb during the second world war - HAROUNI, B (Journal of Human Sciences, 2003)
This article attempts to show the American Government’s duplicity towards the North African colonial problem during the Second World war. This duplicity is to be examined in the approach of the American Government to Vichy France colonial authorities and North African nationalists during the preparation of the invasion of North Africa and during the presence of the Anglo-American expeditionary forces in this area. Indeed, duplicity and realpolitic were the essence of the policy of President Franklin D. Roosevelt and his close collaborators, who, above all, wanted to insure the security of their troops during their passage in North Africa. It is in this perspective that President Roosevelt’s representatives, in Vichy and Algiers promised to restore France in its pre-war integrity; while, at the same time, the American president, associated himself with the British Prime Minister, Winston Churchill, in issuing The Atlantic Charter in which occupied countries and colonised peoples were promised self-determination and freedom.